PSIX-30 Determining Effective Minimum Grade Requirements in Early Prerequisite Courses to Ensure Student Success in Animal Science. (7th December 2018) - Mann, M; Kojima, C; Schneider, L; Saxton, A
Abstract: Many students struggle within an Animal Science curriculum, even when prerequisites are required as preparation. Placing minimum grade requirements on prerequisites (for example, requiring a grade of B or better in a prerequisite course) may improve student success by ensuring that well-prepared students can progress further, while identifying students who should consider alternate majors early in their undergraduate program. To determine effective grade restrictions, performance in prerequisite freshman-level courses was analyzed in conjunction with performance in Animal Anatomy and Physiology (ANSC220; expressed on a grade point scale of 0–4.0, where 2.0 is considered satisfactory). Prerequisite Biology courses are BIOL101 and BIOL102 (a sequence for non-Biology majors), or BIOL150 and BIOL160 (designed for Biology majors). Freshman-level Animal Science courses include ANSC100 and ANSC160. Grades in ANSC220 were compared using separate ANOVAs (SAS Institute, Cary, NC) for students who received grades of A vs. <A, ≥B vs. <B, and ≥C vs. <C in each prerequisite. A dataset containing information on over 700 non-transfer students was utilized; each analysis utilized data only from students who took both the prerequisite course and ANSC220 at the University of Tennessee. The comparisons that determined satisfactory vs. unsatisfactory performance in ANSC220 were identified (see Table 1). Students with less than an A in BIOL101, BIOL102, ANSC100 or ANSC160 performed (on average) unsatisfactorily in ANSC220. Students who received less than a B in BIOL150 or BIOL160 also averaged an unsatisfactory grade in ANSC220. For all prerequisite courses examined, the data suggest that a minimum grade of C would ensure successful progress in ANSC 220. Freshmen who do not reach that benchmark are at high risk of not successfully progressing and should be advised accordingly. These analyses are informative when considering minimum grade requirements to increase student success in challenging majors such as Animal Science.